2016
DOI: 10.15171/mejdd.2016.19
|View full text |Cite
|
Sign up to set email alerts
|

Fever,Weight Loss and Early Satiety due to Gastric Inflammatory Myofibroblastic Tumor; Case Report and Literature Review

Abstract: Gastric inflammatory myofibroblastic tumor (IMT) is a rare tumor with and unpredictable prognosis usually find in young adults. We present an 18-yearold man with gastric IMT. He complained of epigastric pain, intermittent fever and night sweating associated with weight loss since two years ago. Physical examination showed anemic and cachestic features with mild abdominal tenderness in palpitation as well as an abdominal mass in epigastrium. Abdominal CT scan revealed a huge mass that was arising from the stoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Clinical manifestations are often nonspecific. The main manifestations were fatigue, fever, abdominal pain, upper gastrointestinal bleeding, abdominal touch mass, weight reduction, gastroesophageal reflux, pallor, ascites [13]. Microcystic hypochromic anemia may ultimately result from chronic hemorrhagic polypoid ulcer in the stomach IMT [14].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical manifestations are often nonspecific. The main manifestations were fatigue, fever, abdominal pain, upper gastrointestinal bleeding, abdominal touch mass, weight reduction, gastroesophageal reflux, pallor, ascites [13]. Microcystic hypochromic anemia may ultimately result from chronic hemorrhagic polypoid ulcer in the stomach IMT [14].…”
Section: Discussionmentioning
confidence: 99%
“…Our review of 23 gastric IMT cases [ 9 , 11 23 ] reported since 2000 is detailed in Table 1 . The mean tumor size in the 23 cases was 7.4 cm.…”
Section: Discussionmentioning
confidence: 99%
“…IMT of the stomach, especially IMT with metastasis, in adults is extremely rare [ 3 ]. People with gastric IMT usually present non-specific symptoms and signs [ 9 , 10 ]. Even with a thorough diagnostic examination, including CT, ultrasonography, and endoscopic biopsy, an accurate preoperative diagnosis is difficult.…”
Section: Discussionmentioning
confidence: 99%